A evangelização da Igreja em mudança de época, a partir do agir libertador de Jesus, em resistência ao sistema neoliberal - Santos Júnior, Fábio Oliveira dos (2020)
The evangelization of the Church in a changing era,from the liberating action of Jesus, in resistance to the neoliberal system. We live in a visible change of era, marked by so many miseries and injustices of social and political character. It worries us to know if it is really possible to live the ideals of the Kingdom of God, which Jesus Christ, in his liberating action, presented to his contemporaries and to later generations. It is clear that neoliberalism has not been able to solve the underlying problems of a political, social and economic nature that have emerged in the last decades in the societies in which it has been implemented. Rather, it has made people's situations more complex and challenging, if not more unfair and unequal. In the process of its development, neoliberalism has provided a society driven by competitiveness and, not only this, has made the State act in a selective way, making sense of people, especially the poorest, depriving them of their most basic rights. In this sense, it is important to search in Jesus' liberating action for the values that exalt life, especially of the poorest and most miserable, who today no longer have those who represent them in the search to safeguard their dignity, see the indigenous minorities in the context of the pandemic and social distancing. Jesus presents us, through actions and words, an alternative proposal to the dictates of the powerful Roman Empire and the erverse religious domination of his time. Therefore, it is up to the Church - People of God, in its evangelizing process - to adopt the dynamics of the Kingdom announced by him. It is up to the Christian Churches to show the values of this Kingdom through the truthful word and the different forms of resistance to neoliberal logic.